The relationship between sense of coherence and self-efficacy with well-being and mental health—the situation of students at a typical German university during the COVID-19 pandemic and 1 year after the lifting of social restrictions - Kösler, Lisa-Marie; Bauer, Stephanie; Möltner, Andreas; Holm-Hadulla, Rainer M. (Frontiers in Psychology, 2024)
Introduction The present study aims to evaluate the role of sense of coherence and self-efficacy in relation to mental health and well-being, with and without social restrictions due to the COVID-19 pandemic. Additionally, this study seeks to investigate the differences in sense of coherence, self-efficacy, mental health and well-being depending on the manner in which the pandemic is being handled. Methods A total of 27,162 students at Heidelberg University were surveyed via email at two measurement points, once with and once without social restrictions. The survey assessed sense of coherence, self-efficacy, mental health and well-being. To this end, the questionnaires Sense of Coherence Scale, Patient Health Questionnaire, WHO-Wellbeing-Index and the General Self-Efficacy Scale were employed. A total of 2,398 individuals participated in the initial measurement, while 701 individuals participated in the subsequent measurement. Results The lifting of social restrictions has been associated with a notable improvement in well-being and mental health, particularly in the context of depressive syndromes. Further analysis demonstrated a positive correlation between the sense of coherence and self-efficacy at both measurement points, as well as between these two constructs and mental health and well-being. Furthermore, the sense of coherence and self-efficacy were found to account for a notable proportion of the observed variability in mental health and well-being values. Self-efficacy exhibited a significantly higher mean value at the initial measurement time point compared to the subsequent time point. In contrast, no significant difference was observed in the sense of coherence between the two measurement points. Discussion The findings presented here illustrate the significance of social interaction, sense of coherence and self-efficacy for mental health and well-being.